Análise do ethos discursivo dos líderes oposicionistas durante o impeachment de Dilma Rousseff. - Lima, David Jose Andrade (2018)
“The society thinks the way we [the conseervatives] do.” This sentence was said by the President of the then Chamber of Deputies, regarding the brazilian society. Is Brazil really conservative? This research aims to analyze the presence of a conservative ethos in the discourses of the party leaders who suggested the opening of Dilma Vana Rouussef impeachment process, on April 17th, 2016. In order to achieve this goal, this study is based on some of the studies of Maingueneau (2015; 2016) as far as the ethos in discourse is concerned, the notion of political discourse and social imagination according to Charadeau (2006) and the notion of conservatism presented by Burke (2016) and Scruton (2014, 2015, 2017) The specific objectives of this study are: to understand how the conservative ethos works in the speeches; to identify the aspects of the leaders’ discourses that relate to the social imagination; to establish a typification of the ethos in discourse through the speeches of the learders; d) to analyze the discursive strategies used by the party leaders. The texts that compound the Corpus of this research were taken from the 91st record of the Deputy Chamber Session, deliberative meeting, afternoon, of the second ordinary parliamentary session, 55th legislature on April 17, 2016. This research is a qualitative analytical and cross-sectional study and its corpus is formed by the discoureses of the leaders. It was applied the analyzes strategies of the in the management of the relations of the ethos of the ethos in discourse from Maingueneau (2016) : 1) The deletion of the ethos shown: 2) The convergence of the ethos shown and the ethos told; 3) The dissapereance of the ethos told. The results revealed that most of the leaders who suggested the admissibility of Dilma Roussef impeachment is assosciated to a denounce, incompetence, holder and irony ethos, with the porpose of unqualifying her by rejecting her values. The interest of the leaders was attacking the PT government emphasizing its weakness and making it seem ridiculous. It was identified that the leaders were much more concerned about cursing Dilma’s goverment than presenting real and plausible arguments that could allow na understanding in favor of the President’s impeachment. Overall, the discourses analyzed did not present principles based on the modern conservative mind.